Analysis Of Hpp Calculation Using Full Costing And Variable Costing Methods As A Basis For Determining The Selling Price (Case Study CV. Aldiansyah Blessing Mandiri) - Hurriyaturrohman, Hurriyaturrohman; Indupurnahayu, Indupurnahayu; Wijaya, Suma (Jurnal HARMONI: Jurnal Akuntansi dan Keuangan, 2024)
The calculation of the cost of production has a central role for the company especially in paying the selling price of the product. In this context, there are two approaches used the fll costing method and variable costing . this study aims to calculate the cost of production using both method